Redox active dendronized polystyrenes equipped with peripheral triarylamines - Nokami, Toshiki; Musya, Naoki; Morofuji, Tatsuya; Takeda, Keiji; Takumi, Masahiro; Shimizu, Akihiro; Yoshida, Jun-ichi (Beilstein Journal of Organic Chemistry, 2014)
Dendronized polystyrene having peripheral bromo groups was prepared from the dendronization of unfunctionalized polystyrene with dendritic diarylcarbenium ions bearing peripheral bromo groups using the “cation pool” method. The palladium-catalyzed amination of the peripheral bromo groups with diarylamine gave dendronized polystyrene equipped with peripheral triarylamines, which exhibited two sets of reversible redox peaks in the cyclic voltammetry curves.
Keywords: carbocation; cross-coupling; dendrimer; dendronized polymer; redox

(untitled) - Grayson, S. M.; Fréchet, J. M. J. (Chem. Rev., 2001)

(untitled) - Schlüter, A. D.; Rabe, J. P. (Angew. Chem., Int. Ed., 2000)

(untitled) - Schlüter, A. D. (J. Polym. Sci., Part A: Polym. Chem., 2001)

(untitled) - Zhang, A.; Shu, L.; Bo, Z.; Schlüter, A. D. (Macromol. Chem. Phys., 2003)

(untitled) - Frauenrath, H. (Prog. Polym. Sci., 2005)

(untitled) - Lee, C. C.; MacKay, J. A.; Fréchet, J. M. J.; Szoka, F. C. (Nat. Biotechnol., 2005)

(untitled) - Rudick, J. G.; Percec, V. (Acc. Chem. Res., 2008)

(untitled) - Rosen, B. M.; Wilson, C. J.; Wilson, D. A.; Peterca, M.; Imam, M. R.; Percec, V. (Chem. Rev., 2009)

(untitled) - Valério, C.; Fillaut, J.-L.; Ruiz, J.; Guittard, J.; Blais, J.-C.; Astruc, D. (J. Am. Chem. Soc., 1997)

(untitled) - Shu, C.-F.; Shen, H.-M. (J. Mater. Chem., 1997)

(untitled) - Louie, J.; Hartwig, J. F.; Fry, A. J. (J. Am. Chem. Soc., 1997)

(untitled) - Ranasinghe, M. I.; Varnavski, O. P.; Pawlas, J.; Hauck, S. I.; Louie, J.; Hartwig, J. F.; Goodson, T., III (J. Am. Chem. Soc., 2002)

(untitled) - Hagedorn, K. V.; Varnavski, O.; Hartwig, J.; Goodson, T., III (J. Phys. Chem. C, 2008)

(untitled) - Wong, W. W. H.; Jones, D. J.; Yan, C.; Watkins, S. E.; King, S.; Haque, S. A.; Wen, X.; Ghiggino, K. P.; Holmes, A. B. (Org. Lett., 2009)

(untitled) - Bryce, M. R.; Devonport, W.; Goldenberg, L. M.; Wang, C. (Chem. Commun., 1998)

(untitled) - Le Derf, F.; Levillain, E.; Trippé, G.; Gorgues, A.; Sallé, M.; Sebastían, R.-M.; Caminade, A.-M.; Majoral, J.-P. (Angew. Chem., Int. Ed., 2001)

(untitled) - Beeby, A.; Bryce, M. R.; Christensen, C. A.; Cooke, G.; Duclairoir, F. M. A.; Rotello, V. M. (Chem. Commun., 2002)

(untitled) - Godbert, N.; Bryce, M. R. (J. Mater. Chem., 2002)

(untitled) - Astruc, D. (Nat. Chem., 2012)

(untitled) - Boisselier, E.; Shun, A. C. K.; Ruiz, J.; Cloutet, E.; Belin, C.; Astruc, D. (New J. Chem., 2009)

(untitled) - Okajima, M.; Soga, K.; Nokami, T.; Suga, S.; Yoshida, J. (Org. Lett., 2006)

(untitled) - Nokami, T.; Ohata, K.; Inoue, M.; Tsuyama, H.; Shibuya, A.; Soga, K.; Okajima, M.; Suga, S.; Yoshida, J. (J. Am. Chem. Soc., 2008)

(untitled) - Okajima, M.; Soga, S.; Watanabe, T.; Terao, K.; Nokami, T.; Suga, S.; Yoshida, J. (Bull. Chem. Soc. Jpn., 2009)

(untitled) - Terao, K.; Watanabe, T.; Suehiro, T.; Nokami, T.; Yoshida, J. (Tetrahedron Lett., 2010)

(untitled) - Nokami, T.; Watanabe, T.; Musya, N.; Suehiro, T.; Morofuji, T.; Yoshida, J. (Tetrahedron, 2011)

(untitled) - Nokami, T.; Watanabe, T.; Terao, K.; Soga, K.; Ohata, K.; Yoshida, J. (Electrochemistry, 2013)

(untitled) - Nokami, T.; Watanabe, T.; Musya, N.; Morofuji, T.; Tahara, K.; Tobe, Y.; Yoshida, J. (Chem. Commun., 2011)

Proceedings of the PRiME 2012 - Nokami, T.; Musya, N.; Morofuji, T.; Takeda, K.; Yoshida, J. (Honolulu, HI, 5.10.2012-12.10.2012, 2012)

Comprehensive Organic Synthesis - Olah, G. A.; Krishnamurti, R.; Prakash, G. K. S. (Friedel–Crafts Alkylations, 1991)

(untitled) - Littke, A. F.; Fu, G. C. (Angew. Chem., Int. Ed., 1998)

(untitled) - Yoshida, J.; Suga, S.; Suzuki, S.; Kinomura, N.; Yamamoto, A.; Fujiwara, K. (J. Am. Chem. Soc., 1999)

(untitled) - Suga, S.; Suzuki, S.; Yamamoto, A.; Yoshida, J. (J. Am. Chem. Soc., 2000)

(untitled) - Suga, S.; Okajima, M.; Fujiwara, K.; Yoshida, J. (J. Am. Chem. Soc., 2001)

(untitled) - Suga, S.; Watanabe, M.; Yoshida, J. (J. Am. Chem. Soc., 2002)

(untitled) - Yoshida, J.; Suga, S. (Chem. – Eur. J., 2002)

(untitled) - Suga, S.; Nishida, T.; Yamada, D.; Nagaki, A.; Yoshida, J. (J. Am. Chem. Soc., 2004)

(untitled) - Nagaki, A.; Kawamura, K.; Suga, S.; Ando, T.; Sawamoto, M.; Yoshida, J. (J. Am. Chem. Soc., 2004)

(untitled) - Okajima, M.; Suga, S.; Itami, K.; Yoshida, J. (J. Am. Chem. Soc., 2005)

(untitled) - Maruyama, T.; Suga, S.; Yoshida, J. (J. Am. Chem. Soc., 2005)

(untitled) - Nagaki, A.; Togai, M.; Suga, S.; Aoki, N.; Mae, K.; Yoshida, J. (J. Am. Chem. Soc., 2005)

(untitled) - Suga, S.; Matsumoto, K.; Ueoka, K.; Yoshida, J. (J. Am. Chem. Soc., 2006)

(untitled) - Maruyama, T.; Mizuno, Y.; Shimizu, I.; Suga, S.; Yoshida, J. (J. Am. Chem. Soc., 2007)

(untitled) - Ashikari, Y.; Nokami, T.; Yoshida, J. (J. Am. Chem. Soc., 2011)

(untitled) - Ashikari, Y.; Nokami, T.; Yoshida, J. (Org. Lett., 2012)

(untitled) - Ashikari, Y.; Nokami, T.; Yoshida, J. (Org. Biomol. Chem., 2013)

(untitled) - Ashikari, Y.; Shimizu, A.; Nokami, T.; Yoshida, J. (J. Am. Chem. Soc., 2013)

(untitled) - Yoshida, J.; Ashikari, Y.; Matsumoto, K.; Nokami, T. (J. Synth. Org. Chem., Jpn., 2013)

(untitled) - Nelson, R. F.; Adams, R. N. (J. Am. Chem. Soc., 1968)

(untitled) - Diallo, A. K.; Daran, J.-C.; Varret, F.; Ruiz, J.; Astruc, D. (Angew. Chem., Int. Ed., 2009)

(untitled) - Diallo, A. K.; Absalon, S.; Ruiz, J.; Astruc, D. (J. Am. Chem. Soc., 2011)